Duality of the cooperative industry of public passenger transport in the Metropolitan Area of Oaxaca, Mexico - Carmona López, Antonio Maximino (Cooperativismo & Desarrollo, 2024)
The objective of this paper is to analyze the double dimension in which the cooperative industry of public passenger transport in the Metropolitan Area of Oaxaca is developed; the duality is summarized in an internal conflict between the economic rationality and the social objectives of the cooperative. The study was conducted during the year of 2021 with a qualitative approach. The results allowed us to identify three cooperative companies in the public passenger transport industry, which were created in the last century at the initiative of drivers, mechanics, and assistants, who originally worked in private transport companies, with the intention of contributing with their work as the main resource to the constitution of the cooperative. With the passage of time, the cooperative members were replaced by capitalist members who appropriated the concessions and disrupted the cooperative principles with which these companies were created, giving priority to profit over the maintenance of reserve funds and the management of a democratic government within the cooperative. The relationship between cooperative members, now transformed into rentiers, and drivers is based on a verbal agreement of a civil nature that relieves the employers of the labor protection of bus drivers. The subnational government fosters the existence of an oligopolistic market in public passenger transport in the Oaxaca Metropolitan Area and evades its responsibility to assert the right to mobility that has been elevated to constitutional status.
Keywords: Worker cooperative; Industrial economics; Qualitative research